Significant Progress in the Study of African Freshwater Snails Over the Past 260 Years - Matabaro Ziganira; Colleen T. Downs (Ecology and Evolution, 2025)
ABSTRACT Globally, freshwater ecosystems are threatened. Research progress concerning African freshwater snails was reviewed using a systematic review process. Since 1757, the number of publications produced has increased, particularly in the last decade. In the first 50 years (1757–1800), 0.1% of publications on freshwater snails in Africa were conducted, followed by 0% (1801–1850), 3.3% (1851–1900), 3.5% (1901–1950) and 48.7% (1951–2000). The last 23 years (2001–2024) exhibited a large increase (44.3%) in publications of the total conducted. Studies on freshwater snails varied in number across the 10 major African water basins, with the majority of studies in the Nile (21.7%), followed by the Congo Basin (17.6%) and Niger (12.4%). The Orange Basin and Lake Tanganyika also received a high number of studies (10.9%) and (7.2%), respectively. Most freshwater snail study objectives related to conservation and taxonomy (70%), followed by disease vector (20.5%), with genetics/genomic/DNA barcoding/eDNA receiving significant focus as well (5.2%). Studies focusing on geology and palaeontology (2.5%), followed by climate change (1.5%) and machine learning (0.4%). The modern phase in the study of African freshwater snails came around the early 20th century with the discovery of Bulinus truncatus and Biomphalaria alexandrina as intermediate hosts for the parasites causing human schistosomiasis. African freshwater malacology has since then benefited from African and overseas malacologists based at universities and medical laboratories across Africa and overseas. In addition to taxonomic studies, there was a steady rise in contributions relating to ecology, disease vectors, palaeontology and genetics. These contributed knowledge on local endemism and speciation, invasive species, species origins and distribution across African water basins, as well as the spread of infectious diseases and impacts of climate change. In the last decade, there have been shifts in methods with the application of DNA barcoding, genomics, environmental DNA and, most recently, machine learning approaches.